PENINDASAN HAK DAN KEBEBASAN DALAM I KNOW WHY THE CAGED BIRD SINGS KARYA MAYA ANGELOU - MAWU, FRANCO ROLANDO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ  This research entitled â€œRights and Freedom Oppression in Maya Angelouâ€™s I Know Why the Caged Bird Singsâ€ is written to fulfill the requirement of finishing Bachelorâ€™s Degree in English Department Faculty of Humanities Sam Ratulangi University. It focuses on explaining the Rights and Freedom Oppression in the reflection of the main character as a woman. It also aims at identifying and analyzing the effects of Rights and Freedom Oppression to Black women in general.Â  In this research, the writer used the theory of rights by W.J. Sidis (1940), freedom by Henry W. Nevinson (1921), and oppression by Tony Booth (2013). The methodology used in this research is divided into three steps: preparation, data colletction, and data analysis. In preparation, the writer read the whole novel and writings relating to the topic. In data collection, the writer found out the ideas and materials through the dialogues, actions, characters, and narrations in the novel autobiography as the supporting elements. In data analysis, the writer used the intrinsic approach to look at the dialogues, actions, characters, and narrations. Extrinsic approach was also employed through the comparison of the depiction of Americans social condition and Black peopleâ€™s life to analyse the correlation of the data.Â  The results of this research show that the Black people, especially the women, experienced complex oppressions in relation to their rights and freedom as portrayed in Maya Angelouâ€™s I Know Why the Caged Bird Sings. This brings about huge effects on many aspects of their life. Keywords: Autobiography, Maya Angelou, Rights and Freedom Oppression,Â Â  Black Women, Intrinsic and Extrinsic Approaches